The Influence of Accessibility Factors on The Success of Exclusive Breastfeeding in The Working Area of Portibi Public Health Center, North Padang Lawas Regency in 2026 - Dina Herawati; Ica Fauziah Harahap (PT Inovasi Pratama Internasional, 2026)
Breastfeeding is the best investment for biological survival and improving the health, social, and economic development of individuals and nations. Although the global breastfeeding initiation rate is relatively high, only about 40% of infants under 6 months of age receive exclusive breastfeeding, and 45% continue to receive breastfeeding until the age of 24 months (Fadlliyyah, 2019). This study is an observational study with a cross-sectional design that aims to analyze the influence of accessibility factors on the success of exclusive breastfeeding at the Portibi Community Health Center, North Padang Lawas Regency, in 2026. The study was conducted at the Portibi Community Health Center, North Padang Lawas Regency in 2026 with a total of 78 respondents. This study concluded that accessibility factors have a significant effect on the success of exclusive breastfeeding at the Portibi Community Health Center, North Padang Lawas Regency in 2026 (p-value = 0.05).